Green Entrepreneurial Orientation and Green Marketing Towards Business Sustainability: The Role of Corporate Social Responsibility in Bank Syariah Indonesia - Purwoko; Muhammad Ali Fikri (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2026)
Organizations need to adopt green strategies and social responsibility to maintain business sustainability, especially in developing countries such as Indonesia. This study analyzes the influence of green entrepreneurial orientation and green marketing on business sustainability, with corporate social responsibility as the mediating variable. The research employs a quantitative approach, using PLS-SEM, to test seven proposed hypotheses. The total sample for this study consists of 220 respondents from employees of Bank Syariah Indonesia. The study results show that green entrepreneurial orientation and green marketing positively influence business sustainability, but only green marketing significantly influences corporate social responsibility. Corporate social responsibility positively impacts business sustainability and significantly mediates the relationship between green marketing and business sustainability. Still, it does not mediate the relationship between green entrepreneurial orientation and business sustainability. The finding confirms the importance of integrating green marketing strategies and corporate social responsibility in achieving business sustainability. It highlights the role of corporate social responsibility in bridging the gap between green strategies and stakeholder expectations. This study provides theoretical contributions by reinforcing stakeholder theory, as well as practical contributions in formulating sustainable business strategies.